Functional mapping of the 14-3-3 hub protein as a guide to design 14-3-3 molecular glues. Issue 44 (2nd November 2022) - Somsen, Bente A.; Craenmehr, Fenna W. B.; Liu, Wei-Hong W.; Koops, Auke A.; Pennings, Marloes A. M.; Visser, Emira J.; Ottmann, Christian; Cossar, Peter J.; Brunsveld, Luc
Abstract : The functional mapping of a 14-3-3 protein complex, by means of peptide truncations and point mutations, as an approach to identify critical hotspots regions for 14-3-3 molecular glue drug design. Abstract : Molecular glues represent an evolution in drug discovery, however, targeted stabilization of protein complexes remains challenging, owing to a paucity of drug design rules. The functional mapping of hotspots has been critical to protein–protein interaction (PPI) inhibitor research, however, the orthogonal approach to stabilize PPIs has not exploited this information. Utilizing the hub protein 14-3-3 as a case study we demonstrate that functional mapping of hotspots provides a triage map for 14-3-3 molecular glue development. Truncation and mutation studies allowed deconvoluting the energetic contributions of sidechain and backbone interactions of a 14-3-3-binding non-natural peptide. Three central 14-3-3 hotspots were identified and their thermodynamic characteristics profiled. In addition to the phospho-binding pocket; (i) Asn226, (ii) Lys122 and (iii) the hydrophobic patch formed by Leu218, Ile219 and Leu222 were critical for protein complex formation. Exploiting this hotspot information allowed a peptide-based molecular glue that elicits high cooperativity ( α = 36) and selectively stabilizes the 14-3-3/ChREBP PPI to be uniquely developed.